The Implementation of the Problem Based Learning Model with a Contextual Approach to Improve Middle School Students Creative Thinking Skills - Vita Rizky; Elly Arliani; Syarif Hidayatullah (JME (Journal of Mathematics Education), 2026)
This study aims to analyze the effectiveness of implementing the Problem-Based Learning (PBL) model with a contextual approach in improving students’ mathematical creative thinking skills. This research employed a pre-experimental design using a one-group pretest–posttest approach involving 30 eighth-grade students in Yogyakarta, selected through purposive sampling techniques. The research instruments consisted of a creative thinking skills test and observation sheets. The results showed a significant difference between students’ pretest and posttest scores based on the paired-sample t-test (p-value = 0.0001 0.05). Furthermore, the one-sample t-test results indicated that the average creative thinking ability of students had reached the predetermined mastery criteria (p-value = 0.0001 0.05). The proportion test also demonstrated that classical learning mastery was achieved (p-value = 0.010 0.05), with at least 75% of students reaching the mastery criteria. Thus, it can be concluded that the integration of the PBL model with a contextual approach is effective in enhancing students’ mathematical creative thinking skills and supports active engagement in learning